A study on the implementation of the commissioner of building as an adjudicatory body to resolve disputes and protect the right of strata title property purchasers in Malaysia / Hafiizul Mustaqim Mohd Yusof, Nur Syafiq Kamamzzaman and Zulkefli Abd Latib - Mohd Yusof, Hafiizul Mustaqim; Kamamzzaman, Nur Syafiq; Abd Latib, Zulkefli (Faculty of Law, 2012)
This paper aims to examine on the implementation of the Commissioner of Building (COB) as an adjudicatory body to resolve disputes and protect the rights of purchasers in Malaysia as enshrined under the Building and Common Property Act (Maintenance and Management) 2007(BCPMMA). The structure of this paper begins with the background that explains the current function and problems arising from the establishment of the COB. Next, this paper will state the problem statement. This will be followed by the methodology of research. Where will explain the methods adopted by us in completing the proposal. We would then explain the scope, limitation and significance. Further, the literature review will be divided into three frameworks, which are conceptual framework, legal framework and theoretical framework. This will be followed by our conclusion and lastly we will list out the list of references that we used in preparing the research.